Diabetes mellitus is associated with 90-day mortality in old critically ill COVID-19 patients - COVIP Study Group (2023)
Funding Information: Open access funding provided by University of Innsbruck and Medical University of Innsbruck. The support of the study in France by a grant from Fondation Assistance Publique-Hôpitaux de Paris pour la recherche is greatly appreciated. In Norway, the study was supported by a grant from the Health Region West. In addition, the study was funded by a grant from the European Open Science Cloud (EOSC) by the European Commission. No further specific funding was received. Publisher Copyright: © 2023, The Author(s).